Pengaruh Pemberian Sari Kecambah Kacang Hijau terhadap Kadar Malondialdehid pada Ikan Lele Dumbo (Clarias gariepinus) yang Terinfeksi Bakteri Aeromonas hydrophila [Effect of Mung Bean Sprouts Essences against Malondialdehyde Levels In African catfish (Clarias gariepinus) Infected by Bacteria Aeromonas hydrophila ] - Hari Suprapto; Widy Ayunanti; Boedi Setya Rahardja (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract African catfish (Clarias gariepinus) is a type of freshwater fish consumption with elongated body and smooth skin. Bacterial disease that often strikes African catfish and can cause death as well as a cause of primary infection is A.hydrophila. Bacterial infection may be one cause of the synthesis of lipid peroxidation which is an indication of the emergence of free radicals. And the end result of lipid peroxidation is malondialdehyde. Sprouts are the new little plants grow from seeds planted beans. Green bean seed germination will enrich vitamins including vitamin E, green beans or α-tocopherol. Vitamin E in maintaining the stability of the plasma membrane and protects the cell structure against damage caused by free radicals is by blocking the reaction initiation and propagation of lipid peroxidation reactions interrupt. Data analyze of this research was used Varian Analyze (ANAVA) and to found the lowest level was used Duncan Test. The average yield of malondialdehyde levels in the negative control treatment is 0.0386 ng / 100 mg mass, positive control (1 ml Aeromonas hydrophila 105 cfu per 5 liter) is 0.0962 ng / 100 mg mass, sprout extract treatment (0 , 1 ml per fish) is 0.05 ng / 100 mg mass, germination and pollen treatment Aeromonas hydrophila is 0.0626 ng / 100 mg mass. From these results indicate that the highest levels found in the positive control treatment while the lowest levels found in the negative control. These results also suggest that decreased levels of malondialdehyde using pollen germination is very significantly different with P < 0,01.